AN INTRODUCTION TO THE MEGA-DISKS NETWORKS MAPPING - Estrada, Mario Arturo Ruiz (Malaysian Journal of Science, 2015)
This paper proposes a new multidimensional coordinate space that is called â€œThe Mega-Disks Networks Mapping (MDN-Mapping).â€ The MDN-Mapping captures a large amount of information from n-dimensions in the same graphical space and time. Therefore, the MDN-Mapping creates the possibility to visualize a large number of endogenous and exogenous variables that are distributed and interconnected in different Nano-Disks (j), Micro-Disks (k), Sub-Disks (L), and General-Disks (m) without any visual restriction respectively. Now, it is possible to observe how infinity endogenous variables are moving together with infinity exogenous variables simultaneously in the same graphical space. At the same time, we can visualize how all these variables interact together through the visualization a large number of asymmetric spiral-shaped figures with n-faces that keeps changing always. This asymmetric spiral-shaped figures with n-faces can experience anytime an expansion or contraction that depend on different changes from any Nano-Disk (j) until arrive to the Mega-Disk (Î¾) (or the mega-arithmetic mean). Keywords: Econographicology, Multi-Dimensional graphs and Multi-Dimensional Geometry